1999
DOI: 10.1002/hep.510300316
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt compared with endoscopic treatment for prevention of variceal rebleeding: A meta-analysis

Abstract: Endoscopic treatment (ET) is frequently used to prevent variceal rebleeding but this still occurs in about 50% of patients. Recently, transjugular intrahepatic portosystemic shunt (TIPS) has been compared with ET in several trials. Using a meta-analysis, we evaluated randomized trials comparing TIPS to ET assessing prevention of rebleeding, survival, and the effects on resource use and the quality of patients' lives. Medical databases were searched between January 1988 and January 1999 as well as published cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
3
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(170 citation statements)
references
References 40 publications
5
153
3
8
Order By: Relevance
“…82,127,128 Not surprisingly, recent meta-analyses of 11 trials that compared TIPS to endoscopic therapy as first-line therapy show similar results. 129,130 That is, even though rebleeding is significantly less frequent with TIPS, post-treatment encephalopathy occurs significantly more often after TIPS, and there is no difference in mortality between groups. Furthermore, a recent trial showed that, even though pharmacological (propranolol plus nitrates) therapy was less effective than TIPS in preventing rebleeding, it was associated with less encephalopathy, identical survival, and more frequent improvement in Child-Pugh class with lower costs than TIPS.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 99%
“…82,127,128 Not surprisingly, recent meta-analyses of 11 trials that compared TIPS to endoscopic therapy as first-line therapy show similar results. 129,130 That is, even though rebleeding is significantly less frequent with TIPS, post-treatment encephalopathy occurs significantly more often after TIPS, and there is no difference in mortality between groups. Furthermore, a recent trial showed that, even though pharmacological (propranolol plus nitrates) therapy was less effective than TIPS in preventing rebleeding, it was associated with less encephalopathy, identical survival, and more frequent improvement in Child-Pugh class with lower costs than TIPS.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 99%
“…It was reported that the rate of stenosis of shunt was 33-66% within 1 year and that of encephalopathy was 10-30% [1][2]19,22] . In recent years some scholars applied TIPS to portal hypertension secondary to portal thromblization to ensure the patients to have time for further treatments including liver transplanation [26][27][28][29] .…”
Section: Current Status and Application Of Tips In Pvttmentioning
confidence: 99%
“…TIPS is effective in treating patients with hemorrhage, intractable ascites and portal hypertensive gastropathy, and many favorable results and experiences have been obtained as well [1][2][3][4][5][6][7] . TIPS has been widely used for portal hypertension with portal vein thrombosis (PVT), type-III Budd-Chiari syndrome, even bile duct occlusive diseases, and other portal hypertension [8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…A rough estimate of mortality rate in this population from splenic embolization is 1% (compared with a reported 2.8% mortality from transjugular intrahepatic portosystemic shunt). 39,52 Conclusion Splenic embolization is a technique that can be used alone or in conjunction with other treatments for the mitigation of portal hypertension and associated physiological effects of portal hypertension. This technique can be used safely when total embolization volume is 50% and the procedural and periprocedural time periods are covered with antibiotics.…”
Section: Complicationsmentioning
confidence: 99%